2008
DOI: 10.1161/circimaging.107.745919
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Alterations in Senescent Mice and Effect of Exercise Training

Abstract: Background Aging is accompanied by an alteration in myocardial contractility. However, its noninvasive detection is difficult. The effect of chronic exercise on this decrease is unknown. Murine models of senescence are increasingly used to test therapies in aging. We tested whether strain rate imaging detected left ventricular (LV) systolic dysfunction in aging mice and was able to assess a potential improvement after exercise. Methods and Results Young (3 weeks), adult (2 to 3 months), and old (6 to 18 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 51 publications
4
31
0
2
Order By: Relevance
“…However, the interpretation of deformation becomes complex when one moves from the principles of unidirectional forces on single muscle fibers to the multidirectional array of fibers in the human heart, which constantly remodel to adapt to load changes on the one hand and on the other from an isolated system to an intact circulation, where much of the loading conditions of the ventricle are created by the force and extent of ejection itself into a more or less compliant aorta. Early animal studies have proven the intrinsic relationship between strain/strain rate and myocardial contractility using invasive measures of contractility as a gold standard (6,10,24). However, additional studies have shown that both parameters are not only dependent on intrinsic contractile function of the myocardium but are also influenced by ventricular size (17), hypertrophy (8), and load (1,4,22).…”
mentioning
confidence: 99%
“…However, the interpretation of deformation becomes complex when one moves from the principles of unidirectional forces on single muscle fibers to the multidirectional array of fibers in the human heart, which constantly remodel to adapt to load changes on the one hand and on the other from an isolated system to an intact circulation, where much of the loading conditions of the ventricle are created by the force and extent of ejection itself into a more or less compliant aorta. Early animal studies have proven the intrinsic relationship between strain/strain rate and myocardial contractility using invasive measures of contractility as a gold standard (6,10,24). However, additional studies have shown that both parameters are not only dependent on intrinsic contractile function of the myocardium but are also influenced by ventricular size (17), hypertrophy (8), and load (1,4,22).…”
mentioning
confidence: 99%
“…21 In mice, SR measurements are feasible 11 and accurate to quantify regional myocardial function in different pathological conditions. 22 We previously demonstrated that peak systolic SR obtained with TDI technology was closely correlated with the transmural extent of MI 7 and remained stable during a 4-month follow-up after MI. 10 In the present study, we have shown that SR was also significantly correlated with MI size.…”
Section: Sr and MI Sizementioning
confidence: 86%
“…7 and with previous clinical and experimental studies reporting that strain and SR are less subject to load conditions than conventional measurements. 22,25 In the setting of MI models, the superiority of SR over wall thickening may also be explained by 2 mechanisms: (1) regional wall thickening has been shown to become abnormal only when MI affects 30% to 50% of myocardium, 26 and (2) wall thickening measurements may be affected by tethering of normally contracting neighboring segments. 10 …”
Section: Aw Sr Versus Aw Thickeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies on the effect of exercise training on cardiac aging have been based on epidemiological and cross-sectional studies, since longitudinal studies across the lifespan of humans are intricate. In addition, improvements to vertebrate cardiac function following endurance training have also been documented in both young and old animals (Suvorava et al 2004;Derumeaux et al 2008). However, studies on cardiac aging across ages in long-term and longitudinal study designs in mammals are also complicated because of their long lifespan and genetic redundancy.…”
Section: Introductionmentioning
confidence: 99%